PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ISPRING MELALUI PENDEKATAN SAINTIFIK MATERI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN PADA KELAS IV SDN PAKUNDEN 1 - Saniah, Khoirotul Binti; Farida Nurlaila Zunaidah; Mumun Nurmilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to produce ispring-based interactive media that is suitable for use to assist learning activities in science subjects regarding the structure and function of plant parts. The method used in this research is the Research and development (R&D) method using the ADDIE model. The subjects taken in this research were 16 class IV students at SDN Pakunden 1, Kediri city. The data collection technique in this research is by using a questionnaire. The results of this research obtained a validity assessment according to media expert validators in the appearance aspect of layout design, text, images and animation, obtaining a percentage score of 84.6% with the criteria